Web-communities usage for organization of ukrainian scientists' communication - Федушко, Соломія Степанівна; Мельник, Дарина Володимирівна; Сєров, Юрій Олегович (Eastern-European Journal of Enterprise Technologies, 2012)
This paper offers the analysis of web communities as the sources of informational communication. The functional scheme of the community Ukrainian Scientific Internet community (www.nauka-online.org) is developed